EVALUATION THE IMPACT OF HEAVY METALS ON WATER QUALITY IN GANGA RIVER AT VARANASI, INDIA - A. Jazie, Ali (Al-Qadisiyah Journal of Pure Science, 2017)
Day after a day, the increase of heavy metals concentration in the riverine water have dramatically attired anthropogenic activities. Scientist and policy makers in India gave serious attention for the rising level of pollutants and changes in mid-stream water quality of Ganga River. The present investigation was attempted to study water quality of river Ganga and to record the quantitative change in heavy metals in water if any during the three consecutive months of sampling in 2013. A systematic study has been carried out to assess the impact of heavy metal concentration on water quality of river Ganga in Varanasi city. 36 water samples from four sampling stations i.e. By pass bridge upstream, Assi Ghat, Dashswamedh Ghat, and Raj Ghat bridge downstream, were collected and analyzed for Temperature, pH, concentrations of Cr, Ni, Cu, As, Cd, Pb in (Î¼g.L-1). The results from this study indicated significant accumulation of these heavy metals in the riverine water. The order of heavy metals accumulation in the riverine water was As > Pb > Cu >Ni > Cr > Cd. The analytical data indicates that all heavy metals studied are found to be in excess than the prescribed limit in some water samples of the study areas as compared to World Health Organization standards (WHOS) and toxicity reference value (TRV) for fresh water proposed by USEPA except Ni.